Analisis Penggunaan Digital Marketing sebagai Metode Pemasaran untuk Menarik Pelanggan dalam Usaha Mikro Kecil dan Menengah (UMKM) - Arum Nurcahya, Wilma; Arqy Ahmadi, Mirzam (PENG: Jurnal Ekonomi dan Manajemen, 2025)
With the rapid development of technology, MSMEs need to adapt and utilize digital platforms to increase their competitiveness in the global market. At this time, MSME business actors often face difficulties in applying digital marketing in their businesses, such as a lack of knowledge and how to use digital marketing well, lack of human resources and limited capital are the difficulties that MSME players have to face. The aim of this research is to examine the appropriate use of digital marketing media for MSMEs to develop their businesses, attract customers and gain loyalty from their consumers. This research will be carried out using qualitative methods where researchers will examine previous research to then draw conclusions about existing problems. The results of the study found that the use of social media is a cost-effective technology, this can provide opportunities for MSMEs to be able to communicate with their consumers widely and at low costs. Digital marketing is an effective marketing tool in developing MSMEs, but it requires improved skills, technology and good adaptation so that it can be utilized optimally.